Letter : Aid for Spanish trade unionists - Hallsworth, Joseph
030-0071-001 TELEPHONE RUSHOLME 2804-8 (five Lines) Telegrams: "Nudawn", Phone. Manchester Money Orders to be made payable at Manchester Regd. Trade Union No. 1798ST. Approved Society for National Health Insurance N° 296 NATIONAL UNION of DISTRIBUTIVE ALLIED WORKERS Affiliated to the British and Scottish Trades Union Congresses, Labour Party, International Clothing Workers Federation, International Transport Workers Federation, International Federation of Commercial, Clerical and Technical Employees, International Federation of Trade Unions, International Federation of General Factory Workers, Food and Drink Trades International Federation J. Hallsworth W.A. Robinson) General Secretaries Registered Office: Oakley, Wilmslow Road, Fallowfield, Manchester, 14. In replying please quote 6625/RAC/EK 12th September 1938 The General Secretary, Trades Union Congress, Transport House (South Block), Smith Square, LONDON, S.W.1. Dear Sir, Aid for Spanish Trade Unionists At our Executive Council meeting at Blackpool yesterday the resolution of the Trades Union Congress on Spain was considered, when it was decided to forward to the International Solidarity Fund the sum of £1,000 "as a contribution in aid of the Spanish Trade Union Movement." A cheque for the amount named is enclosed herewith, for which I shall be glad to have your receipt worded as set out above within quotation marks. I make this request in order that this financial transaction shall be kept within the four corners of our rules. I am also to inform you that the voluntary subscriptions that we have been collecting for some weeks past from our members will continue and a communication is going to all branches asking them to intensify the efforts they are making to secure an even more ready response than has been obtained hitherto. These subscriptions are, of course, being sent on to your office as they flow in to this office from the branches, and this method of collection and transmission will continue. Yours sincerely, J Hallsworth Industrial General Secretary. Enclosure 292/946/30/71